MARX'S ECOLOGY IN THE 21st CENTURY. (1st April 2010) - Unknown
Abstract : The most pressing problem confronting humanity in the 21st century is the ecological crisis. The "problem of nature" is really a problem of capital, as natural cycles are turned into broken linear processes geared to private accumulation. Important advances in ecosocialist theory illuminate the continuing importance of Marx's materialist and metabolic approach for studying the dialectical interchange between humans and nature and the creation of ecological rifts within ecosystems. Additionally, Marx's ecology serves as a foundation for understanding environmental degradation, given his critique of capital as a whole and his focus on the contradiction between use value and exchange value (which facilitates the expansion of private riches at the expense of public wealth, i.e., the Lauderdale Paradox). In stark contrast to the market mechanisms proposed to address the ecological crisis, which place profit above protecting nature, Marx's ecology stresses the necessity of establishing a social order that sustains the conditions of life for future generations.